2022
DOI: 10.1007/s11071-022-07985-4
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model reveals the influence of NPIs and vaccination on SARS-CoV-2 Omicron Variant

Abstract: An SVEIR SARS-CoV-2 Omicron variant model is proposed to provide some insights to coordinate non-pharmaceutical interventions (NPIs) and vaccination. Mathematically, we define the basic reproduction number and the effective reproduction number to measure the infection potential of Omicron variant and formulate an optimal disease control strategy. Our inversion results imply that the sick period of Omicron variant in the United States is longer than that of Delta variant in India. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A study by Wang and coworkers reported a mathematical model for the effect of vaccines and NPIs. They reported that even full vaccination at the population level was not sufficient for herd immunity when the efficiency of vaccines was low, and as such, NPIs were still indispensable [ 49 ]. A systematic review by Brito and coworkers reported that some less disruptive NPIs, such as mask wearing requirements, were also effective [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang and coworkers reported a mathematical model for the effect of vaccines and NPIs. They reported that even full vaccination at the population level was not sufficient for herd immunity when the efficiency of vaccines was low, and as such, NPIs were still indispensable [ 49 ]. A systematic review by Brito and coworkers reported that some less disruptive NPIs, such as mask wearing requirements, were also effective [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found vaccination alone could not mitigate the epidemic, especially in the early stage of mass vaccination campaigns. Many modeling studies have emphasized the necessity of maintaining the intensity of NPIs when the vaccination coverage is low ( 10 , 16 , 20 ). A more important finding in this study was that mass vaccination campaigns in the early stage could even increase the risk of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies focused on the early stage of the pandemic with the SARS-CoV-2 origin virus and the Alpha variant being dominant ( 3 , 17 , 18 ), however, evidence on the effectiveness in successive waves was relatively few, especially for the period of Omicron variant epidemic. Some modeling studies have discussed the varying effect of NPIs due to Omicron ( 19 , 20 ), but the clues were not strong enough because the assumed population features and transmission parameters would be different from the real world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A network model with periodic transmission rate was developed to analyze the effects of heterogeneity and waning immunity on measles transmission and to theoretically examine the threshold dynamics 28 . Mathematical modeling of infectious disease is studied a lot in recent times 29 35 , for example.…”
Section: Introductionmentioning
confidence: 99%